2015
DOI: 10.3389/fphys.2015.00404
|View full text |Cite
|
Sign up to set email alerts
|

Sprint Acceleration Mechanics: The Major Role of Hamstrings in Horizontal Force Production

Abstract: Recent literature supports the importance of horizontal ground reaction force (GRF) production for sprint acceleration performance. Modeling and clinical studies have shown that the hip extensors are very likely contributors to sprint acceleration performance. We experimentally tested the role of the hip extensors in horizontal GRF production during short, maximal, treadmill sprint accelerations. Torque capabilities of the knee and hip extensors and flexors were assessed using an isokinetic dynamometer in 14 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
219
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(262 citation statements)
references
References 87 publications
(134 reference statements)
8
219
1
10
Order By: Relevance
“…A smaller touchdown distance and lower horizontal velocity of the foot (relative to the ground) are considered to be mechanisms to reduce braking impulse, by creating a more “active touchdown” . In a previous study by Morin et al, an athlete's ability to activate their hamstring muscles during late swing phase along with the capacity to produce high eccentric hamstring torques was associated with higher average antero‐posterior forces during the stance phase. Moreover, energy absorption at the knee during late swing (presumably involving work carried out by hamstrings) was previously suggested to be responsible for continuing acceleration at near maximal velocities, which could be linked to a decrease in forward horizontal foot velocity prior to touchdown and a more active touchdown.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller touchdown distance and lower horizontal velocity of the foot (relative to the ground) are considered to be mechanisms to reduce braking impulse, by creating a more “active touchdown” . In a previous study by Morin et al, an athlete's ability to activate their hamstring muscles during late swing phase along with the capacity to produce high eccentric hamstring torques was associated with higher average antero‐posterior forces during the stance phase. Moreover, energy absorption at the knee during late swing (presumably involving work carried out by hamstrings) was previously suggested to be responsible for continuing acceleration at near maximal velocities, which could be linked to a decrease in forward horizontal foot velocity prior to touchdown and a more active touchdown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its potential role in preventing posterior thigh muscle strains, hamstring muscle strength has been suggested as an important factor to improve sprinting performance in soccer as a horizontal force producer [15,16]. During the acceleration phase of sprinting, forward orientation of ground reaction force (GRF) has been shown to be the most powerful determinant of field sprint performance compared to the overall magnitude of vertical or resultant GRF [17]. Recently, Morin et al [17] have shown that hamstring EMG activity during the swing phase and eccentric knee flexor peak torque were related to the amount of horizontal GRF produced during treadmill sprint accelerations converting the hamstrings as a key muscular determinant of sprint acceleration performance.…”
Section: Introductionmentioning
confidence: 99%
“…During the acceleration phase of sprinting, forward orientation of ground reaction force (GRF) has been shown to be the most powerful determinant of field sprint performance compared to the overall magnitude of vertical or resultant GRF [17]. Recently, Morin et al [17] have shown that hamstring EMG activity during the swing phase and eccentric knee flexor peak torque were related to the amount of horizontal GRF produced during treadmill sprint accelerations converting the hamstrings as a key muscular determinant of sprint acceleration performance. These results suggest that the conjunction of hip extensors (hamstrings in particular) torque capability and degree of activation during the swing phase, is a key muscular determinant of sprint acceleration performance [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the measures that Wiewelhove et al implemented to assess peripheral muscle fatigue (lower limb muscle soreness and CMJ height) likely reflect significant fatigue of other muscles, but not the RF. This is not surprising as many other hip/knee extensor and flexor muscles are involved in sprint-related exercises (Morin et al, 2015). If these other muscles were tested with TMG we argue that TMG markers would have been sensitive enough to detect peripheral muscle fatigue.…”
mentioning
confidence: 93%